Profitabilitas Dan Likuiditas Terhadap Kinerja Keuangan Sebelum Dan Sesudah Initial Public Offering (IPO) - Aminar Sutra Dewi; Resi Novalia (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
This study aims to identify and analyze the effect of profitability and liquidity on the financial performance of companies conducting an Initial Public Offering (IPO) listed on the using secondary data obtained from the Indonesian Stock Exchange website. The total population is 252 companies and the sample is 45 companies with a Indonesia Stock Exchange for the 2017-2021 period. This type of research is quantitative research total of 135 observations. Sampling using purposive sampling technique. Methods of data analysis using Ordinary Least Square, with a multiple regression model approach, statistical t-test and different test. The results of the study show that: Profitability/NPM has a significant positive effect on the financial performance of companies conducting an Initial Public Offering (IPO) listed on the Indonesia Stock Exchange for the 2017-2021 period. Liquidity/Cash Ratio has a positive and insignificant effect on the financial performance of companies conducting an Initial Public Offering (IPO) listed on the Indonesia Stock Exchange for the 2017-2021 period. There is no difference in profitability/NPM after and before the Initial Public Offering (IPO). There are differences in liquidity/ cash ratios after and before the Initial Public Offering (IPO).